Kali kerberti Weber 1913 - Melo, Marcelo R. S. (Zenodo, 2008)
Kali kerberti (Weber 1913) (Figs. 1 B, 3, 4; Tables 1, 3 and 4) Odontonema kerberti Weber 1913: 149 [original description; type locality Banda Sea, Indonesia 5 ° 39 ’ S, 122 ° 12 ’ E, Siboga sta. 208, 1886 m; holotype ZMA 104006]; Norman 1929: 544 [key to species, distribution based on original description]; de Beaufort and Chapman 1951: 10 –11 [record based on original description]; Norman 1966: 366 –367 [key to genera of Chiasmodontidae and list of species]. Kali kerberti Smith 1965: 572 –574, figure 2 [species validated as a member of Kali , redescription included]. Dolichodon normani Parr 1931 a: 46 –47, figure 18 [original description, type locality 16 ° 14 ’ N, 99 ° 36 ’ W, 3291 m, 31 – VI– 1926, R/V Pawnee , holotype YPM 2693]. NEW COMBINATION. Hemicyclodon normani Parr 1931 b: 1962 [replacement name for Dolichodon , preoccupied]. Kali normani Smith 1965 [species validation and synonymized Odontonema with Kali ]; Johnson 1969: 589 –590, figure 1 [revision of the genus and key to the species]; Johnson and Cohen 1974: 42 –44 [revision of the genus, diagnosis and brief description]; Johnson and Keene 1986: 734, figure 228.8 [key to the species]; Smith (in press) [key to species]; Johnson and Keene 1990: 9030 – 904 [record of eastern tropical Atlantic species]; Mooi and Paxton 2001: 3495 –3496 [list of Pacific species]; Figueiredo et a. 2003: 93 [checklist of Brazilian species]; McEachran and Sutton 2003: 1742 –1743 [list of Atlantic species]; Mundy 2005: 455 –456 [checklist of Hawaiian species]; Hardy 2005: 1902, 1912– 1913 [identification of larvae]; Hardy 2007: 1312 [identification of larvae]. Material examined. 72 specimens, including holotypes of Kali kerberti and K. normani . Atlantic, Slope Water: MCZ 60724, 1, 64.9 mm, 38 ° 49 ' N, 71 ° 40 ' W, 600–800 m, 30 –IV– 1982, R/V Oceanus . North Sargasso Sea: USNM 207596, 1, 113.2 mm, 32 °04’ N, 63 ° 58 ’ W, 0–1025 m, 22 –VIII– 1971, Ocean Acre expedition; USNM 207619, 1, 69.8 mm, 33 °04’ N, 64 ° 37 ’ W, 0–1060 m, 4 –VII– 1967, Ocean Acre expedition. South Sargasso Sea: ZUMC P. 6530, 1, 99.6 mm, 26 ° 58 ’ N, 56 ° 58 ’ W, 5 –V– 1922, R/V Dana . Lesser Antillean Province: USNM 207622, 1, 133.1 mm, 11 ° 38 ’ N, 51 ° 52 ’ W, 1103 m, 31 –V– 1965, R/V Trident . Amazonian: UW 21249, 1, 148.0 mm (cs), 3 °00’ S, 26 ° 16 ’ W, 0–2000 m, 3 – II – 1968, R/V Walther Herwig . South Atlantic Subtropical: MNRJ 26712, 1, 133.8 mm, 21 °07’ S, 39 ° 46 ’ W, 1686–1699 m, 8 –VII– 2000 R/V Thalassa . Guinean Province: MCZ 61018, 1, 73.2 mm, 0°00’N, 19 ° 45 ’W, 0–1164 m, 20 –IV– 1965, R/V Trident UF 220004, 1, 91.2 mm, 0° 25 ’ S, 5 °09’ W, 850 m, 23 –V– 1965, R/V Pillsbury USNM 207614, 3, 131.6 – 161.8 mm, 7 °00’ N, 20 ° 58 ’ W, 0–1330 m, 14 –IV– 1971, R/ V Walther Herwig . Indian: ZUMC P. 6531, 1, 93.5 mm, 8 ° 24 ’ S, 42 ° 54 ’ E, 24 –XII– 1929, R/V Dana . Pacific, Western Pacific: AMS 24859010, 1, 192.68 mm, 33 ° 43 ’ S, 152 °03’ E, 0–1135 m, 16 –X– 1984, F R/V Kapala AMS 36466019, 1, 93.13 mm, 16 °00’ N, 122 ° 59 ’ E, 4384–4667 m, 28 –IX– 1995, J. Paxton col.; SIO 76–166 –60, 1, 104.2 mm, 14 ° 14 ' S, 150 °54.0' E, 6 –III– 1975, R/V Alpha Helix SIO 77–171 –60, 1, 96.5 mm, 04° 40 ' S, 125 ° 32 ' E, 0–1500 m, 26 – VIII– 1976, R/V Thomas Washington ZMA 104006, holotype (ca. 65.0 mm), 5 ° 39 ’ S, 122 ° 12 ’ E, 1886 m, Siboga Expedition col. Pacific Plate: AMNH 22566, 1, 147.8 mm, 19 ° 40 ’ N, 156 ° 20 ’ W [coordinates inferred], 1975, O. Barton col.; AMS 17853001, 1, 79.6 mm, 1 °00’ N, 170 °00’ W, 0–1000 m, 16 –III– 1966, R/ V Coriolis FMNH 88149, 1, 152.1 mm, 21 ° 23 ’ N, 158 ° 18 ’ W, 20 – II – 1971, R.E. Young col.; FMNH 88150, 1, 117.1 mm, 21 ° 23 ’ N, 158 ° 18 ’ W, 4 –IX– 1972, R.E. Young col.; HUMZ 144032, 1, 118.3 mm, 20 °00’ N, 156 °00’ W [coordinates inferred], 5 – II – 1996, unknown col.; MCZ 56850, 1, 127.6 mm, 21 ° 20 ’ N, 158 ° 20 ’ W [coordinates inferred], 2 – II – 1973, R/V Teritu SIO 60–216 –60, 1, 69.1 mm, 10 °09’ N, 128 ° 30 ’ W, 0–1540 m, 24 –VI– 1960, R/V Spencer F. Baird SIO 60–229 –60, 1, 82.0 mm, 01° 39 ’ S, 133 ° 35 ’ W, 0–2326 m, 29 –VI– 1960, R/V Spencer F. Baird SIO 69–342 –60, 1, 148.9 mm, 17 ° 49 ’ S, 110 ° 19 ’ W, 0–1100 m, 29 –III– 1969, R/ V Thomas Washington SIO 73 – 36 –60, 1, 132.1 mm, 9 ° 28 ’ S, 124 ° 12 ’ W, 13 –XII– 1970, R/V Thomas Washington SIO 73 – 43 –60, 1, 128.3 mm, 10 ° 40 ’ S, 123 ° 38 ’W, 17 –XII– 1970, R/V Thomas Washington SIO 73– 328 –60, 1, 137.6 mm, 27 ° 59 ’ N, 154 ° 41 ’W, 20 –VI– 1973, R/V Thomas Washington SIO 88–154 –60, 1, 112.4 mm, 19 ° 18 ’ N, 168 ° 59 ' W, + 700 m, 5 –III– 1987, R/V Atlantis II USNM 207600, 1, 196.4 mm, 20 ° 15 ’ N, 155 ° 31 ’ W, 823 m, 30 –III– 1968, R/V Townsend Cromwell USNM 271063, 1, 144.8 mm (female), 7 °00’ N, 150 ° 22 ’ W, 0–850 m, 17 –I– 1978, R/V Kana Keoki USMN 272723, 1, 131.3 mm, 11 ° 48 ’ N, 138 ° 11 ’ W, 885 m, 01–III– 1976, R/V Oceanographer USMN 288994, 1, 64.7 mm, 11 ° 42 ’ N, 138 ° 12 ’ W, 0–860 m, Sep 09– IX– 1975, R/V Oceanographer USNM 289024, 1, 117.6 mm, 9 °02’ N, 150 ° 11 ’ W, 0–950 m, 7 –I– 1978, R/V Kana Keoki USNM 289228, 2, 70.8–71.8 mm, 13 ° 30 ’ N, 150 °00’ W, 0–950 m, 7 –I– 1978, R/V Kana Keoki . Eastern Pacific: CAS 61408, 2, 76.8–105.3 mm, 02° 26 ’ S, 88 ° 46 ’ W, 0–300 m, 27 / 28 –V– 1966, R/V Anton Bruun LACM 8736, 1, 104.9 mm, 23 °00’ N, 109 ° 40 ’ W [coordinates inferred], 30 –III– 1964, R/V Ve le ro LACM 8863 –1, 1, 120.8 mm, 24 °00’ N, 109 ° 40 ’ W [coordinates inferred], 18 –IV– 1964, R/V Ve le ro LACM 9036 –6, 1, 136.8 mm, 33 ° 30 ’ N, 118 °00’ W [coordinates inferred], unknown col.; LACM 9651 –3, 1, 123.6 mm, 28 ° 30 ' N, 118 °00' W [coordinates inferred], 3 –VIII– 1966, R/V Ve le ro LACM 31104 –6, 2, 135.0– 61.8 mm, 16 ° 30 ’ N, 100 °00’ W [coordinates inferred], 13 –I– 1970, R/V Ve le ro LACM 31107 –8, 1, 137.2 mm, 20 ° 30 ’ N, 106 °00’ W [coordinates inferred], 15 –I– 1970, R/V Ve le ro LACM 31110 –7, 1, 142.3 mm, 20 ° 30 ’ N, 106 °00’ W [coordinates inferred], 15 –I– 1970, R/V Ve le ro LACM 31111 –7, 2, 54.2 –71.0 mm, 21 °00’ N, 109 °00’ W [coordinates inferred], 17 –I– 1970, R/V Ve le ro LACM 31112 –5, 1, 122.5 mm, 21 °00’ N, 109 °00’ W [coordinates inferred], 17 –I– 1970, R/V Vel ero LACM 31117 –9, 1, 131.0 mm, 20 ° 30 ’ N, 106 °00’ W [coordinates inferred], 19 –I– 1970, R/V Vel ero LACM 31118, 1, 129.4 mm, 20 ° 30 ’ N, 106 °00’ W [coordinates inferred], 19 –I– 1970, R/V Vel ero LACM 31119 –6, 1, 149.3 mm, 21 ° 15 ’ N, 106 ° 15 ’ W [coordinates inferred], 19 –I– 1970, R/V Ve le ro LACM 31120 –10, 1, 127.1 mm, 21 ° 15 ’ N, 106 ° 15 ’ W [coordinates inferred], 19 –I– 1970, R/V Vel e ro LACM 31130 –8, 1, 71.8 mm, 21 °00’ N, 109 °00’ W [coordinates inferred], 23 –I– 1970, R/V Vel ero LACM 31126 –12, 1, 130.1 mm, 21 °00’ N, 109 °00’ W [coordinates inferred], 21 –I– 1970, R/V Ve le ro SIO 51–90 –60, 1, 114.7 mm, 25 °48.0' N, 114 °46.0' W, 2212 m, 21 / 22 –III– 1951, R/V Paolina SIO 56–79 –60, 2, 112.9 –148.0 mm, 28 ° 58 ’ N, 118 ° 11 ’ W, 29 –VIII–1956, 1152 m, R/V Paolina SIO 56–83 –60, 1, 104.1 mm, 28 °55.0' N, 118 ° 11.2 ' W, 30 –VIII–1956, 1152 m, R/V Paolina SIO 57–140 –60, 1, 86.9 mm, 22 ° 43 ’ N, 111 °06’ W, 15 –VII– 1957, R/V Orca SIO 60–203 –60, 1, 137.0 mm, 26 ° 52 ’ N, 120 °05’ W, 0–2000 m, 17 –VI– 1960, R/V Spencer F. Baird SIO 65–236 –60, 1, 128.1 mm, 22 ° 35 ’ N, 110 ° 13 ’ W, 29 – VI– 1965, R/V Horizon SIO 65–244 –60, 1, 120.7 mm, 23 °08’ N, 109 ° 13 ’ W, 1 / 2 –VII– 1965, R/V Horizon SIO 68 – 52 –60, 1, 121.9 mm, 22 ° 40 ’ N, 109 °07’ W, 9 –I– 1968, R/V Thomas Washington SIO 75–227 –60, 1, 139.5 mm, 1 ° 19 ’ N, 98 °01’ W, 0–200 m, 24 –VI– 1971, R/V David Starr Jordan USNM 207606, 1, 141.4 mm (female), 2 ° 26 ’ S, 88 ° 46 ’ W, 0–400 m, 28 –V– 1966, R/V Anton Bruun YPM 2693, holotype of Kali normani , 101.8 mm, 16 ° 14 ’ N, 99 ° 36 ’ W, 3291 m, 31 –VI– 1926, R/V Pawnee . Diagnosis. Kali kerberti can be distinguished from all species of Kali , except K. macrodon by the ascending process of premaxilla with a strong concavity limited anteriorly by bony crest ( vs. ascending process of premaxilla flat or with gentle concavity, anterior bony crest absent). It further differs from K. colubrina , K. falx , K. indica , and K. parri by the teeth in lateral series of premaxilla and dentary 12–25, type 4, needle-like ( vs. teeth in lateral series of premaxilla with ventral attachment, recurved in K. parri five to 11, caniniform, type 4, slightly curved in K. indica and K. falx and recurved in K. colubrina ); from K. macrura , teeth in lateral series of premaxilla and dentary type 4, needle-like, extending to the end of dentigerous area, teeth with ventral attachment absent in lateral series ( vs. teeth in lateral series of premaxilla and dentary need-like in anterior third and fourth, respectively, followed by teeth with ventral attachment, recurved in posterior areas). Kali kerberti can be distinguished from K. macrodon by the teeth in mesial series of premaxilla and dentary, four to five, modally five ( vs. teeth in mesial series of premaxilla teeth six to nine, modally seven, of and dentary seven to nine, modally eight). Description. Moderate-sized species of Kali , largest specimen examined 196.4 mm SL. Meristic data summarized in table 2, and morphometric in table 4. General body pattern as described for genus. Dentition. Teeth present on premaxilla, dentary, palatine, upper and lower pharyngobranchials; premaxilla and dentary as illustrated in figure 1 B and summarized in table 1. Tooth crown length 36.5–46.7 % in tooth length. Premaxilla elongated, strongly arched in lateral view, with teeth arranged in two series: lateral and mesial. Lateral series in single row; teeth small and numerous, type 4, needle-like, without flange, closely spaced, increasing in size from anterior to posterior on first half, gradually decreasing in size to posterior end. Mesial series in irregular single row; first tooth type 4, conical, slightly curved, with flange, not developed into fang; following teeth fang-like, recurved with ventral attachment, largest tooth 28.1–29.5 % in premaxillary length; widely spaced, decreasing in size from anterior to posterior; base of first mesial tooth at anterior ventral portion of premaxilla, second tooth (first fang) at level of anterior nostril, third tooth at posterior nostril, fourth tooth at anterior margin of eye, fifth tooth at posterior margin of eye, and sixth tooth slightly posterior to middle of premaxilla. Dentary elongated, moderately arched in lateral view; teeth arranged in two series: lateral and mesial. Lateral series in single row; teeth type 4, needle-like, without flange, closely spaced, increasing in size from anterior to posterior on first half, gradually decreasing in size to posterior end. Teeth in mesial series with ventral attachment, recurved, fang-like, largest tooth 23.8–25.8 % in dentary, with flange; teeth widely spaced, decreasing in size from anterior to posterior. Base of first tooth opposite to gap between first and second teeth in mesial series of premaxilla; remaining teeth opposite to gaps between premaxillary fangs. Palatine teeth type 4, conical, slender, with short flange, in single row. Lower pharyngeal teeth type 4, needle-like, without flange, in single row; upper pharyngeal teeth type 4, needle-like, without flange, in two rows. Gill rakers tooth-like, type 1, conical, slender, without flange, individually attached to bone, or in small patches of two; present on first, second and third arches; absent on first hypobranchial, basihyal and basibranchials. Color. Skin covering body fragile, missing in most specimens, description based on USNM 207601, AMNH 225946 and an unpreserved specimen (Fig. 4 B, C). Epidermis black, thin and fragile, completely destroyed or restricted to small patches in all specimens examined; dermis thick and gelatinous, whitish or clear gray, with widely spaced melanophores. Peritoneum transparent, with moderate concentration of melanophores. Orobranchial chamber, gill arches and gill filaments pale, melanophores absent; red blood vessels visible in fresh specimen. Distribution. World-wide in the equatorial, tropical, and subtropical regions: in the Atlantic from 38 ° N to 21 ° S; a single record in the western Indian at 8 ° S, 31 ° S; in the Pacific 27 ° N to 33 ° S (Fig. 3). Bathymetric distribution. Meso- and bathypelagic zones; more frequently recorded in depths between 800 and 2500 m (mean 1343 m). Shallowest record at 200 m; deepest at 4465 m. Remarks. Johnson (1969: 338) considered Kali kerberti to be a junior synonym of Kali indica without examining the holotype, based on meristic data and the “strong developed gap between the expanded apices of the premaxillaries” – a characteristic not considered to be useful herein. Johnson and Cohen (1974) after examining the holotype followed Johnson’s previous conclusion. Those authors surprising ignored Smith’s (1964) detailed-rich redescription of the species. Smith (1965: 573) noticed that “a few slender widely separated small tooth-like gillrakers [sic] are present on the first arch”, which is also confirmed herein: the epibranchial has one tooth, the ceratobranchial four, and the hypobranchial zero (teeth-like gill rakers are absent in K. indica ). Smith (1965: 574) description of the dentition in the holotype of K. kerberti also agrees with the data presented herein: “four long blunt moderately stout flexible slightly curved fangs” in the upper jaw ( vs. three fangs in K. indica ); “between these [fangs] are several much smaller sharp teeeth [sic]”, regarding the teeth in lateral series ( vs. teeth in lateral series not numerous and sharp, 7–11 in Kali indica vs. 15–33 in K. kerberti ); and in lower jaw “four of the larger fangs, and between these a series of long slender sharp recumbent inwardly directed flexible hair-like [=needle-like] teeth” ( vs. fangs 3, lateral series not needle-like in K. indica ). This combination of characteristics is unique and clearly diagnostic for K. kerberti , therefore the species is considered as valid. : Published as part of Melo, Marcelo R. S., 2008, The genus Kali Lloyd (Chiasmodontidae: Teleostei) with description of new two species, and the revalidation of K. kerberti Weber, pp. 1-33 in Zootaxa 1747 on pages 10-13, DOI: 10.5281/zenodo.181658 : {"references": ["Weber, M. (1913) Die Fische der Siboga-Expedition. Leiden, E. J. Brill, Fische Siboga Expedition: i - xii + 1 - 710, Pls. 1 - 12.", "Norman, J. R. (1929) The teleostean fishes of the family Chiasmodontidae. The Annals and Magazine of Natural History, Series 10, 3, 529 - 544.", "de Beaufort, L. F. & Chapman, W. M. (1951) The fishes of the Indo-Australian archipelago. Volume IX, Percomorphi (concluded), Blennoidea. E. J. Brill, Leiden, 484 pp.", "Norman, J. R. (1966) A d raft synopsis of the Orders, Families and Genera of recent fishes and fish-like vertebrates (excluding Ostariophysi, Scleroparei, Ammodytidae and a few other Families, notably Centrarchidae, Percidae, and Cichlidae) covering literature up to 1938, and, as far it was available to the author, from 1939 to 1944. Trustees of the British Museum (Natural History), London, 649 pp.", "Smith, J. L. B. (1965) An interesting new fish of the family Chiasmodontidae from South Africa, with redescription of Odontonema kerberti Weber, 1913. Annals and Magazine of Natural History, Series 13, 7, 567 - 574.", "Parr, A. E. (1931 a) Deepsea fishes from off the western coast of North and Central America. With keys to the genera Stomias, Diplophos, Melamphaes and Bregmaceros, and a revision of the Macropterus group of the genus Lampanyctus. Bulletin of the Bingham Oceanographic Collection, 2, 1 - 53.", "Parr, A. E. (1931 b) A substitute name for Dolichodon Parr, a genus of deep-sea fishes. Copeia, 1931, 162.", "Johnson, R. K. (1969) A review of the fish genus Kali (Perciformes: Chiasmodontidae). Copeia, 1969, 386 - 391.", "Johnson, R. K. & Cohen, D. M. (1974) Results of the research cruises of FRV Walther Herwig to South America. XXX. Revision of the chiasmodontid fish genera Dysalotus and Kali, with descriptions of two new species. Archiv fur Fischereiwissenschaft, 25, 13 - 46.", "Johnson, R. K. & Keene, M. J. (1986) Chiasmodontidae. In: Smith, M. M. & Heemstra, P. C. (Eds) Smith's sea fishes. Johannesburg, Macmillan South Africa, pp: 731 - 735.", "Johnson, R. K. & Keene, M. J. (1990) Chiasmodontidae. In: Quero, J. C., Hureau, J. C., Karrer, C., Post, A. & Saldanha, L. (Eds) Check - list of the fishes of the eastern tropical Atlantic. Paris, UNESCO, pp. 899 - 904.", "Mooi, R. D. & Paxton, J. R. (2001) Family Chiasmodontidae. In: Carpenter, K. E. & Niem, V. H. (Eds) Species identification guide for fishery purposes. The living marine resources of the western central Pacific. Bony fishes part 6 (Labridae to Latimeriidae), estuarine crocodiles, sea turtles, sea snakes and marine mammals. FAO, Rome, pp. 3495 - 3496.", "Figueiredo, J. L., Santos, A. P. & Menezes, N. A. (2003) Familia Chiasmodontidae. In: Menezes, N. A., Buckup, P. A., Figueiredo, J. L. & Moura, R. L. (Eds.) Catalogo das especies de peixes marinhos do Brasil. Museu de Zoologia de Universidade de Sao Paulo, Brazil, pp 93 - 94.", "McEachran, J. D. & Sutton, T. (2003) Chiasmodontidae. In: Carpenter, K. E. (Ed) The living marine resources of the Western Central Atlantic. Volume 3: Bony fishes part 2 (Opistognathidae to Molidae). FAO species identification guide for fishery purposes and American Society of Ichthyologist and Herpetologists Special Publication No. 5. FAO, Rome, pp 1742 - 1743.", "Mundy, B. C. (2005) Checklist of the fishes of the Hawaiian Archipelago. Bishop Museum Bulletin in Zoology 6, Bishop Museum Press, Honolulu, 704 p.", "Hardy, J. D. (2005) Chiasmodontidae: swallowers. In: Richards W. J. (Ed.) Early stages of the Atlantic fishes - an identification guide to the Western Central North Atlantic. Taylor and Francis Group, Portland, pp. 1901 - 1915.", "Hardy, J. D. (2007) Early Stages of Fishes in the Western North Atlantic Ocean, (Davis Strait, Southern Greenland and Flemish Cap to Cape Hatteras). Northwestern Atlantic Fisheries Organization, Nova Scotia, 1696 pp."]}